2019
DOI: 10.3390/su11174690
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Values of Willingness to Pay for Water Quality Improvement: Insights from Chia Lagoon, Malawi

Abstract: Water resources in the Chia lagoon in Malawi experience a possible threat to sustainability. Communities are seeking alternatives to improve water quality in the lagoon. This study quantified the communities’ willingness-to-pay (WTP) and their influencing factors while using contingent valuation (CV) techniques. A wide range of data collection procedures, including focus group discussions, key informant interviews, field observation, and CV survey, were employed. A sample of 300 households was randomly selecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 86 publications
7
32
0
1
Order By: Relevance
“…This implies that the second question depends on the answer obtained in the first question, and much more information is obtained from the individual than with the single-bounded approach, thus implying a more complex econometric analysis. Recent studies, such as those by Lopez-Feldman [62], Mesa-Jurado et al [26], Islam et al [61], and Makwinja et al [63] have used this method in various contexts but with similar research purposes. Subsequently, the model used in this study is briefly described.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the second question depends on the answer obtained in the first question, and much more information is obtained from the individual than with the single-bounded approach, thus implying a more complex econometric analysis. Recent studies, such as those by Lopez-Feldman [62], Mesa-Jurado et al [26], Islam et al [61], and Makwinja et al [63] have used this method in various contexts but with similar research purposes. Subsequently, the model used in this study is briefly described.…”
Section: Methodsmentioning
confidence: 99%
“…After the initial bid, the second bid price offered is higher or lower depending on the answer obtained to the first bid, as explained in previous sub-section. Similar groups of questions are used in previous recent studies, such as Martín-Ortega et al [38], Makwinja et al [63], Jian et al [65], and Asibey et al [66], among others.…”
Section: Sampling Process and Survey Designmentioning
confidence: 97%
“…Prasher et al [19] and Do and Bennett [20] added that distance between the users and the natural resource can significantly influence one's WTP-thus, the closer the user to the natural resource, the higher the WTP. Other factors that have been documented to have a positive influence on the WTP include educational level, age, and knowledge about natural resource [19,21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, our results could not establish a statistically significant relationship this insignificant finding is consistent with (Gulyani et al, 2005b). Several studies have shown a correlation between the between income and payment for water services, wealthier households are more likely to pay for connection to piped water supply and other social services while poorer households rely on alternative sources such as boreholes, dams, rivers, streams and rain water (Kanyoka et al, 2008;Makwinja et al, 2019;Rotich et al, 2018). Other studies have also found an insignificant relationships associated with underreporting of actual household income (Rahman et al, 2017).…”
Section: Factors That Influence Household Willingness To Pay For Imprmentioning
confidence: 99%